SIKAP REMAJA MASJID TERHADAP NORMA KELlJARGA KECIL - Subardhi, Subardhi (Jurnal Cakrawala Pendidikan, 2001)
This investigation was designed to examine the relationship that exist among Mosqueyoungster's knowledge of Islam, Mosque youngster's knowledge of population problem andMosque youngster's attitude toward small family norm. This relationship would be studiedin corellational form by independently or collectively.The subject of this research was the Mosque youngster's at Surabaya. This researchused a survey method. The sample included 210 persons. The data were collected usingsimple and multiple regression analysis.The finding of this research were, first, a positive highly significant correlation existedbetween mosque youngster's knowledge of Islam and mosque youngster's attitude towardsmall family norm. Second, a positive highly significant correlation existed between mosqueyoungster's knowledge of population problems and mosque youngster's attitude towardsmall family norm. Third, a positive highly significant multiple correlation existed amongmosque youngster's knowledge of Islam and mosque youngster's knowledge of populationproblem collectively and mosque youngster's attitude toward small family norm.